Influence of concentrate levels in diet and body biotypes on productive variables of Guzera beef cattle - Homem, Antonio Carlos [UNESP]; Neto, Marcos Chiquitelli [UNESP]; Pinheiro, Rafael Silvio Bonilha [UNESP]; Filho, William Koury [UNESP]; Estremote, Marcelo [UNESP]; Camerro, Leandro Zuccherato [UNESP]; Donofre, Ana Carolina; Filho, José Nicolau Prospero Puoli [UNESP] (Universidade Estadual de Londrina, 2016)
The goal of this study was evaluate diets (50 or 80% of concentrate) and body biotypes (late or early) on performance, behavior, carcass condition, meat quality, and feed cost estimates in feedlot finishing Guzera beef cattle. Use of concentrates in the diet may improve performance and carcass fat scores in ruminant animals, but Guzera beef cattle may be more efficient in forage conversion, which directly influences the economic viability of the production system. We evaluated 32 non-castrated male Guzera beef cattle at 32±2 months of age. The experimental design was completely randomized with four treatments and six replicates in a 2 × 2 factorial design (2 diets × 2 body biotypes). Initial and final body weights were 459.4±31.2 kg and 566.7±40.8 kg, respectively. There was no change (P > 0.05) in dry matter intake, feed conversion, or daily weight gain when the concentrate in the diet was increased to 80%. Animals fed a diet with 80% of concentrate spent less time (P < 0.05) ruminating (17.8±6.3 vs. 6.3±2.7% of the assessed time). Body biotype did not alter the variables. The rise from 50 to 80% in the proportion of dietary concentrate increased carcass fat, with positive returns in the production process, even given the reduction in rumination, which can lead to poor welfare of animals consuming 80% of dietary concentrate. Body biotype did not affect the variables studied, but it is worth emphasizing that the age at slaughter of these animals probably influenced this result. Thus, selection of the best diet should be based on feeding cost, and in accordance with the cost estimated in this study, the diet with 80% of concentrate is the most suitable for feedlot finished Guzera beef cattle.
Keywords: Behavior; Carcass condition; Costs; Feedlot; Meat quality; Performance